HUBUNGAN BERBAGAI MACAM FAKTOR RISIKO KANKER KOLOREKTAL DENGAN MASA SURVIVAL PASIEN KANKER KOLOREKTAL DI RSUD NGANJUK - Listya Santoso, Ardanna; Hernanda, Pratika Yuhyi; Sugeng, Maria Widijanti; Sanjaya, Ayling (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2025)
Background: Colorectal cancer is one of the types of cancer with a high mortality rate worldwide, including in Indonesia. Objective: To analyze the relationship between various risk factors (history of smoking, obesity, alcohol consumption, family history of cancer, and comorbid diseases) and the survival of colorectal cancer patients at Nganjuk General Hospital. Methods: This study used an observational analytic design with a cross-sectional approach. Data were taken from the medical records of 42 colorectal cancer patients treated at Nganjuk General Hospital. Results: The findings showed that none of the patients had a history of smoking, obesity, alcohol consumption, or family history of cancer. However, there is a significant relationship between comorbid diseases and the survival of colorectal cancer patients (p-value = 0.048). Conclusion: The importance of managing comorbid diseases to improve the survival of colorectal cancer patients.